Breeding rice for salinity tolerance and salt-affected soils in Africa: a review - Mheni, Nafeti Titus; Kilasi, Newton; Quiloy, Fergie Ann; Heredia, Maria Cristina; Bilaro, Atugonza; Meliyo, Joel; Dixit, Shalabh; Nchimbi Msolla, Susan (Informa UK Limited, 2024)
Salinity is one of the main factors that limit rice production globally. In Sub Saharan Africa, soil salinity has affected many countries. Understanding the available screening techniques and the mechanisms of salinity tolerance in rice is very important for dealing with soil salinity problem. This review summarizes the extent of soil salinity problems in some of the affected African countries and the available salt stress-tolerant rice genotypes. The problems, challenges and opportunities of salt-affected soils in Sub Saharan Africa are thoroughly described in this review, which also looks at breeding techniques which have been used for developing rice cultivars adapted to salt stress. Among the best option to deal with salinity-related problems is through the use of tolerant rice varieties, as many other available management approaches are not economically feasible for small-scale farmers. Also, the review discusses different approaches, both conventional and molecular breeding approaches that have greatly enhanced the current rice breeders’ toolboxes for developing salt-tolerant rice varieties. The review suggests that more efforts are required to leverage conventional breeding with molecular techniques for speedy identification of tolerant cultivars, useful markers and quantitative trait loci (QTLs). It is recommended that it is crucial to reinforce collaborative efforts and continuous investment in research, capacity building, and knowledge sharing for developing improved rice tolerant cultivars in order to fully address salinity problems in African.